Education to Increase Public Awareness Regarding Plastic Waste - Permadi Permadi; Risky Setiawan; Wahyudin Wahyudin; Jojor Taruli Siringo (Global Sustainability Research Institute, 2026)
Plastic waste management has become an increasingly critical environmental issue in urban areas due to rising population density and household activities. This community service program was conducted in Kampung Kadu Sempur, Kadu Village, Curug District, Tangerang Regency, with a focus on improving community awareness and knowledge regarding plastic waste management. The main problem faced by the community was the low level of awareness in disposing of and sorting plastic waste, which led to waste accumulation, environmental pollution, and the loss of potential economic value from plastic waste. This program aimed to enhance public understanding of the environmental impacts of plastic waste and to encourage more responsible and sustainable waste management behavior. The methods employed included field observation, the development and installation of visual educational media such as information boards on plastic decomposition time and educational banners, community counseling sessions, as well as post-activity monitoring and evaluation. The results indicate an improvement in community knowledge regarding the types of plastic waste, their decomposition periods, and their environmental impacts. However, consistent behavioral change in waste sorting practices has not yet been optimally achieved.